‘Invierno’, cultivar of xoconostle for central Mexico - Gallegos-Vázquez Clemente; Scheinvar, Leia; Silos-Espino Héctor; Fuentes-Hernandez, Alma Delia; Núñez-Colín Carlos A.; Olalde-Parra, Gabriel (Revista Mexicana de Ciencias Agrícolas, 2018)
A new horticultural form of the genus Opuntia described by Miller (Cactaceae), located in the municipality of Villa de Tezontepec, State of Hidalgo, Mexico, known as xononostle ‘Invierno’. Was evaluated from 2008 to 2010 and found that their mature pads are broadly elliptic, with 8-9 series of borders, with 3-4 spines by areola; blooms once a year and its commercialmaturityisreachedinthemonthofAprilnextyear that f lowering occurs. The fruit of ‘Invierno’ is medium (76.2 cm) in size and oval, with slightly sunken f loral scar epidermis with bright light green with red-orange spots, salmon walls, wide (10.3 mm, characteristic of xoconostles), acidic (pH 4.3), semi-dry to dry and tasteless funiculus orange, firm, medium juiciness and low sugar content (4.4 °Brix) and with few fully developed seeds (137). The average yield on three-year evaluation was 8 727 kg ha-1 and remain off for more than 15 months on the ground, af ter the onset of ripening, which gives it a comparative advantage over varieties xoconostle cuaresmeño Manzano and grown in central Mexico. This variety is being validated under the conditions of Villa Tezontepec, Hidalgo and Calera, Zacatecas to establish their suitability and potential to increase the varietal standard for the commercial production of cactus in the semiarid highlands of Mexico.